2013
DOI: 10.1016/j.bandl.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease disrupts both automatic and controlled processing of action verbs

Abstract: The problem of how word meaning is processed in the brain has been a topic of intense investigation in cognitive neuroscience. While considerable correlational evidence exists for the involvement of sensory-motor systems in conceptual processing, it is still unclear whether they play a causal role. We investigated this issue by comparing the performance of patients with Parkinson’s disease (PD) with that of age-matched controls when processing action and abstract verbs. To examine the effects of task demands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
103
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 86 publications
13
103
2
1
Order By: Relevance
“…amyotrophic lateral sclerosis), and patients with this pathology have significantly worse understanding of action verbs than object nouns (Bak & Hodges, 2004;Hillis et al, 2006;Grossman et al, 2008). Similarly, Parkinson's disease interferes, albeit indirectly, with the operations of the precentral motor cortices, and it has been argued that patients with this disorder have selectively impaired appreciation of action verbs (Boulenger et al, 2008a;Fernandino et al, 2013;Ibáñez et al, 2013).…”
Section: Functional Relevancementioning
confidence: 99%
“…amyotrophic lateral sclerosis), and patients with this pathology have significantly worse understanding of action verbs than object nouns (Bak & Hodges, 2004;Hillis et al, 2006;Grossman et al, 2008). Similarly, Parkinson's disease interferes, albeit indirectly, with the operations of the precentral motor cortices, and it has been argued that patients with this disorder have selectively impaired appreciation of action verbs (Boulenger et al, 2008a;Fernandino et al, 2013;Ibáñez et al, 2013).…”
Section: Functional Relevancementioning
confidence: 99%
“…verbs [34]. Finally, a study comparing motorlanguage coupling in early PD, neuromyelitis optica, and acute transverse myelitis, indicated that deficits in the integration of action verbs and manual actions result from atrophy of cortico-subcortical motor network system, and not from peripheral (musculoskeletal) motor system affectation [35].…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 99%
“…However, using the KDT, Ibáñez et al [48] found that early PD patients also exhibited impaired action-semantics in the absence of executive deficits. For their own part, Fernandino et al [34] showed that deficits in processing action-semantics, as compared showing the proposed frontotemporal basal ganglia-thalamocortical network (light yellow, blue, and green regions of interest, respectively). The arrows indicate the suggested principal flow of information involved in action-verb processing through two main overlap subcircuits.…”
Section: Action-language Impairments In Parkinson's Diseasementioning
confidence: 99%
“…Boulenger et al (2008) found priming effects for action verbs in PD varied as a function of Levodopa uptake (medication improving motor impairment in PD). Fernandino et al (2013a) removed the grammatical confound in noun-verb comparisons by comparing PD patients and healthy controls on action verb and abstract verb processing. Compared to healthy controls, patients performed worse with action verbs than abstract verbs, reflecting impairment in processing action language rather than the grammatical category of verbs.…”
mentioning
confidence: 99%